Currency Redenomination: Economic Solution or Nominal Illusion? A Systematic Review - Maharani Maharani; Melati Sukma Dewi Labusang; Aldi Laana Laronggo; Jaja Awal Bakti; Deva Enggrina (Jambura Accounting Review, 2025)
This study aims to systematically review the academic literature on currency redenomination as a domestic monetary policy and evaluate whether it represents an effective economic solution or merely a nominal adjustment. Using a systematic literature review (SLR) approach, the study analyzes peer-reviewed journal articles published between 2000 and 2025, indexed in Scopus, ScienceDirect, and Emerald, applying the PRISMA framework and clear selection criteria. Seven core articles were examined using qualitative thematic analysis. The findings indicate that currency redenomination does not directly change real purchasing power or macroeconomic fundamentals; rather, its success depends heavily on macroeconomic stability, institutional readiness, political legitimacy, and effective public communication. Under conditions of low and stable inflation, redenomination can improve transactional efficiency, accounting simplicity, and business productivity. At the microeconomic level, some studies report increased firm profitability, although the impacts are often context-specific. Psychologically, redenomination is associated with the money illusion effect, influencing price perceptions and consumer behavior, yet effective public education campaigns can significantly reduce these biases. Overall, currency redenomination should be understood as a strategic political–economic policy that may succeed under specific conditions rather than a universal solution to monetary challenges.